Navigating Two Worlds: Experiences of Counsellors who Integrate Aboriginal Traditional Healing Practices - Oulanova, Olga; Moodley, Roy (Canadian Journal of Counselling and Psychotherapy, 2010)
There is revival in the use of traditional healing among Canadian Aboriginal communities and the therapeutic benefits of these practices have received much research attention. An argument is repeatedly made for incorporating indigenous healing into clinical interventions, yet recommendations on how this may be accomplished are lacking. The present study aimed to address this limitation. We interviewed nine mental health professionals who routinely employ both Western psychological interventions and Aboriginal traditional healing practices. Grounded Theory data analysis identified four core themes and led to a model that illustrates participants’ integrative efforts. Implications for counsellors working with Aboriginal clients are addressed. Les pratiques traditionnelles de guérison refont surface dans les communautés Autochtones du Canada et les bénéfices de ces pratiques ont déjà fait l’objet de plusieurs études. Malgré les suggestions répétées d’intégrer les pratiques de guérison traditionnelles en pratique cliniques, il n’existe pas de lignes directrices pour guider ce processus. Cette étude se penche sur ce sujet. Nous avons interviewer neuf praticiens en santé mentale qui intègre des pratiques traditionnelles de guérison Autochtones dans leur pratique psychologique. En utilisant la théorie à base empirique, nous avons identifié quatre thèmes principaux et élaboré un modèle qui illustre comment les participants arrivent à cette intégration. Les implications pour les conseillers qui travaillent avec des clients Autochtones sont discutées.